823 Compliance with TED Stocking Usage in Surgical Patients in ELHT Surgical Wards. (19th August 2022) - Abdel Jalil, O; Yasin, M; Lim, S; Abdelrahim, A
Abstract: Introduction: Anti-embolic stocking (AES) is elastic stocking specifically designed to reduce the risk of VTE events. Multiple studies proved the effectiveness of AES in reducing the risk of DVT in hospitalized patients undergoing surgerical procedures. Aim: Our Audit aimed to examine our doctors' compliance in prescribing AES, as well as the nursing staff's compliance in distributing the stockings to patients. We also aimed at investigating if any discrepancies are present between the different surgical wards in our hospital, or between weekdays and weekends. Method: Data were collected by bedside observation of patients to see if they are wearing the stockings as well as inspecting the prescription charts. The data collection occurred over 2 weeks with a random day picked on a weekday and on a weekend each week. Each surgical ward was reported separately to compare the results. After presenting the results, a poster was distributed to educate doctors and nursing staff about the importance and true contraindications of AES. In addition, a sticker indicating the AES was added to the patient's board to check. A re-audit was done after one month. Results: Initially, average in compliance with wearing the stocking was 50–70%, while the prescription rate was 44–84%. No major changes were noted between wards and between different days of the week. After the changes, slight improvement in the compliance was noted but not in prescription. Conclusion: Educating staff and doctors about the importance of AES is essential for compliance, in addition to the need for repeated audits to check sustainability of changes.